International Year of Light and Light-based Technologies - Gupta, Gagan (SCHOOL SCIENCE, 2015)
The International Year of Light and Light based Technologies (IYL 2015) is a global initiative adopted by the United Nations to raise awareness of how optical technologies promote sustainable development and provide solutions to worldwide challenges in almost all areas. The proposal for celebrating 2015 as International Year of Light was first brought by United Nations Educational, Scientific and Cultural Organisation (UNESCO) delegates from Ghana and Mexico to the UNESCO Executive Board. Supported by 28 Board members, the resolution proposing IYL 2015 was placed before the 190th session of the UNESCO Executive Board held at Paris in October 2012. Recognising the importance of light and light-based technologies in the lives of the citizens of the world and for the future development of global society on many levels, the resolution was finally adopted by the UN in the 68th session of its General Assembly held in Paris in December 2013 (see Fig.1). Endorsed by a number of international scientific unions, IYL 2015 has partnership from more than 85 countries. Its global secretariat is located at the International Centre of Theoretical Physics (ICTP), TRIESTE, Italy, in collaboration with the UNESCO International Basic Sciences Program. In its resolution for adopting the IYL 2015, the General Assembly also considered that the light-based technologies and designs can play an important role in the achievement of greater energy efficiency, in particular by limiting energy waste, and in the reduction of light pollution, which is a key to preservation of dark skies.